Alterations in inflammatory markers after a 12-week exercise program in individuals with schizophrenia—a randomized controlled trial - Bigseth, Therese Torgersen; Engh, John Abel; Andersen, Eivind; Bang-Kittilsen, Gry; Egeland, Jens; Falk, Ragnhild Sørum; Holmen, Tom Langerud; Mordal, Jon; Nielsen, Jimmi; Ueland, Thor; Vang, Torkel; Fredriksen, Mats (Frontiers in Psychiatry, 2023)
Background In individuals with schizophrenia, inflammation is associated with depression, somatic comorbidity and reduced quality of life. Physical exercise is known to reduce inflammation in other populations, but we have only limited knowledge in the field of schizophrenia. We assessed inflammatory markers in plasma samples from individuals with schizophrenia participating in an exercise intervention randomized controlled trial. We hypothesized that (i) physical exercise would reduce levels of inflammatory markers and (ii) elevated inflammatory status at baseline would be associated with improvement in cardiorespiratory fitness (CRF) following intervention. Method Eighty-two individuals with schizophrenia were randomized to a 12-week intervention of either high-intensity interval training (HIIT, n = 43) or active video gaming (AVG, n = 39). Participants were assessed at baseline, post intervention and four months later. The associations between exercise and the inflammatory markers soluble urokinase plasminogen activator receptor, c-reactive protein, tumor necrosis factor (TNF), soluble TNF receptor 1 and interleukin 6 (IL-6) were estimated using linear mixed effect models for repeated measures. For estimating associations between baseline inflammation and change in CRF, we used linear regression models. Results Our main findings were (i) TNF and IL-6 increased during the intervention period for both groups. Other inflammatory markers did not change during the exercise intervention period; (ii) baseline inflammatory status did not influence change in CRF during intervention, except for a positive association between baseline IL-6 levels and improvements of CRF to post intervention for both groups. Conclusion In our study, HIIT and AVG for 12-weeks had no reducing effect on inflammatory markers. Patients with high baseline IL-6 levels had a positive change in CRF during intervention. In order to increase our knowledge regarding association between inflammatory markers and exercise in individuals with schizophrenia, larger studies with more frequent and longer exercise bout duration are warranted.